Attendance of ice hockey matches in the Czech Extraliga - Lahvička, Jiří, 1975- (2010)
This paper uses data about 3,640 matches played in the seasons 2000/01-2009/10 to explain individual match attendance of the top Czech ice hockey competition -- the Extraliga. Some interesting results are that fans decide whether to attend based on the detailed information about the home team, but use just the easily observable information about the away team; that a match having no impact on the final season outcome is much less attended; that televising a match decreases attendances of all matches played on the same day, but there is no negative next-day effect; that both very good and very bad weather decreases attendance; and that if two home matches are played in a short time period, their attendance is lower with likely higher impact on the second match. Substitution of ice hockey with soccer is investigated on several different levels -- while ice hockey and soccer are definitely long-term substitutes, there are mixed results for same-day substitution. Modernization of ice hockey arenas is identified as the key factor behind the almost 20% attendance growth in the analyzed period. This paper also presents a new realistic method of modeling seasonal uncertainty based on Monte Carlo simulation that does not rely on ex post information.